Kriteria Kepala Negara menurut Hukum Tata Negara Islam (Studi Kasus Putusan mk no. 90/puu-xxi/2023) - Khairuddin; Ulfah Alfiyah Darajat; Muhamad Azmi; Ahmad Musthafa A'zhom (CV. Creative Tugu Pena, 2024)
The issue regarding the minimum age requirements for presidential and vice presidential candidates as stated in Constitutional Court Decision No. 90/PUU-XXI/2023 has been on the public's lips continuously in the past year. There have been many reports regarding the results of this decision, and most recently violations of the Constitutional Court judges' code of ethics were discovered in the decision-making process. This case has been widely researched (especially in the 2024 time period), but this case has never been formulated in a research problem formulation from the perspective of Islamic constitutional law, which actually has an intensity regarding the conception of the head of state (president and vice president). Therefore, the question regarding how Islamic constitutional law views this case is important to formulate as a research problem. Based on the research results, the Constitutional Court Decision No. 90/PUU-XXI/2023 according to Islamic constitutional law is not contradictory because the criteria for the head of state in Islamic constitutional law do not refer to age limits but to physical and spiritual perfection. As for the head of state's conception, Islamic constitutional law is very dependent on the system of government adopted by the country. So the decision of the Constitutional Court case was returned to the discussion of constitutional law that applies in Indonesia.